Weak vs strong knowledge spillover effects. Evidence from geographic distribution of innovative startup in Italy - Barboza, Gustavo; Pede, Valerien (Southern Regional Science Association, 2024)
This paper introduces the concepts of weak and strong knowledge spillover effects within the context of the Knowledge Spillover Theory of Entrepreneurship. In this context, the fundamental idea of our proposition is to provide a comprehensive analysis of the factors and conditions promoting and supporting entrepreneurship development at the regional and provincial level using a unique unbalanced panel database, consisting of 9242 Italian Innovative startups for the period 2008-2018. In general terms, we argue that the evidence from our unbalanced panel dataset indicates that these dynamics are as follows. First, spillover effects deriving from competition are initially strong at the province level, and later decay to weak spillover effects at the regional level. Second, in terms of specialization (intra-industry) spillover effects, they are initially strong at the provincial level, and later become weak at the regional level. Third, spillover effects deriving from diversity (inter-industry) are predominantly strong at the regional level, yet weak at the provincial level of aggregation. At the provincial level, higher levels of competition result in strong knowledge spillover effects leading to higher new firm formation, with weak knowledge spillover effects deriving from specialization. Furthermore, in line with the Knowledge Spillover Theory of Entrepreneurship, the existence of non-homogeneous distribution of opportunities and related knowledge spillover effects create heterogeneity of patterns of new firm formation across different units of geographic aggregation. These results provide evidence of constraint potential for growth that remains a puzzle and challenge for academics and policymakers.